Bridging gap between agro-industrial waste, biodiversity and mycelium-based biocomposites: Understanding their properties by multiscale methodology - Isabel Enriquez-Medina; Isaac Rodas-Ortiz; Isabella Bedoya-Garcia; AnaMaria Velasquez-Godoy; Carlos Alvarez-Vasco; Andres Ceballos Bermudez (Journal of Bioresources and Bioproducts)
A multiscale methodology approach was employed integrating microscopic analysis of the biomasses present in the biocomposite (lignocellulosic and fungal) to understand their macroscopic response in terms of physical and mechanical properties. Colombian native strain Ganoderma gibbosum, used for the first time in the production of biocomposites was cultivated on peach palm fruit peel flour and sugar cane bagasse wet dust, individually and as a mixture. During the solid-state fermentation were monitoring the change that occurred in substrate composition such as glucan, arabinoxylan, and lignin through biomass compositional analysis using structural carbohydrates and lignin. Moreover, fungal biomass formation was monitored via scanning electron microscopy. The resulting biocomposites underwent characterization through flexural and water absorption tests. Our findings indicated that G. gibbosum primarily degraded the polysaccharides in each of the evaluated media. However, lignin degradation to 15.06 g/g was only observed in the mixture biocomposite of peach palm fruit peel fluor and sugarcane bagasse wet dust in a ratio of 1꞉1, accompanied by a reduction in glucan and arabinoxylan weights to 26.1 and 7.72 g/g, respectively. This polymer degradation, combined with a protein-rich source in the mixture biocomposite of peach palm fruit peel fluor and sugarcane bagasse wet dust in a ratio of 1꞉1, facilitated the production of a fungal skin (biological matrix) with a high hyphal density of 65%, contributing to Young's modulus of 3.83 MPa, elongation without failure, and low water absorption rate in this biocomposite (55%). The lignocellulosic biomass in the culture media acted as a filler for mechanical interlocking with the matrix and provided attachment points for water absorption. Thus, our study establishes a connection between the microscopic scale and the macroscopic behavior of this biocomposite, assessing structural carbohydrates and lignin analysis during solid-state fermentation (SSF), laying the groundwork for a more customized design of mycelium-based biocomposites. Finally, this study demonstrates the possibility of tailoring nutrient composition by designing their culture media to obtain physical-mechanical properties according to the application requirement.